2011
DOI: 10.1093/toxsci/kfr175
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Aryl Hydrocarbon Receptor Suppresses Sensitization in a Mouse Peanut Allergy Model

Abstract: Food allergy is an increasing health problem in Western countries. Previously, it has been shown that the intensity of food allergic reactions can be regulated by regulatory T (T(reg)) cells. In addition, it has been shown that activation of the aryl hydrocarbon receptor (AhR) regulates T-cell responses by induction of T(reg) cells. Therefore, we hypothesized that activation of the AhR pathway can suppress development of food allergic responses through the induction of T(reg) cells. This was investigated by us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(42 citation statements)
references
References 50 publications
4
37
1
Order By: Relevance
“…Strikingly, FICZ-dependent formation of ROS observed in our experiments would also be in accordance and contribute to the enhancement of the overall inflammatory acute response observed in young allergic patients (32). Alternatively, repetitive exposure to AhR-ligand pollutants could suppress MC degranulation and attenuate the allergic response in favor of other types MCmediated responses (e.g., inflammatory responses) by directly acting on AhR-mediated MC responsiveness (10). Consistently, MC "desensitization" through a repetitive AhR activation may suggest an association with approaching therapies to desensitize patients (especially children) that develop severe IgE-mediated anaphylactic responses against dietary compounds (33).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Strikingly, FICZ-dependent formation of ROS observed in our experiments would also be in accordance and contribute to the enhancement of the overall inflammatory acute response observed in young allergic patients (32). Alternatively, repetitive exposure to AhR-ligand pollutants could suppress MC degranulation and attenuate the allergic response in favor of other types MCmediated responses (e.g., inflammatory responses) by directly acting on AhR-mediated MC responsiveness (10). Consistently, MC "desensitization" through a repetitive AhR activation may suggest an association with approaching therapies to desensitize patients (especially children) that develop severe IgE-mediated anaphylactic responses against dietary compounds (33).…”
Section: Discussionsupporting
confidence: 83%
“…Therefore, AhR expression and its possible role in modulating MC functions may have significant implications for the outcome of inflammatory pathologies where effector T cell/Treg cell balance is compromised. Interestingly, a recent study shows that the activation of AhR suppresses the development of Th2-mediated food allergic response by inducing Treg cell skewing (10). However, these data do not exclude that AhR engagement could directly affect the function of allergy effector cells, namely MCs, beyond T cells.…”
mentioning
confidence: 93%
“…TCDD treatment only weakly affected the number of Tregs, consistent with the literature (Kerkvliet, 2009b;Negishi et al, 2005). We also found that TCDD exposure decreased the levels of pro-inflammatory cytokines IL-6 and IL-22 and increased the levels of the anti-inflammatory cytokines IL-13 and IL-12p70 (Table 2), consistent with TCDD-induced suppression of immune hypersensitivity phenotype in the mouse model of peanut allergy (Schulz et al, 2011).…”
Section: Body Weight Showed No Difference After Tcdd Exposuresupporting
confidence: 90%
“…13,14 In the context of allergic hypersensitivity, AhR agonists inhibit Th2-mediated cytokine production and allergic responses in mouse models of atopic dermatitis, food allergy and asthma-like disease. 10,15,16 However, when using whole animal models, it is difficult to determine whether the effects of AhR ligands are due to direct effects on T cells or to effects on T-cell programming by antigen-presenting cells. Interestingly, wild-type recipients of adoptively transferred AhR-deficient T cells displayed TCDD-induced inhibition of T-cell proliferation in response to influenza virus, 11,17 suggesting that antigenpresenting cells play a key a role in AhR modulation of T-cell function.…”
Section: M M U N O L O G Y O R I G I N a L A R T I C L Ementioning
confidence: 99%